177 Differences in Patient Characteristics and Surgical Outcomes in Inpatient vs Outpatient Surgery for Peyronie's Disease: Contemporary Data from the National Surgical Quality Improvement Program Database. Issue 1 (1st April 2022) - Raheem, T.M.; Fustok, J.; Voznesensky, I.; Pandit, A.; Machado, B.; Payakachat, N.; Davis, R.; Benson, C.; Raheem, O.
ABSTRACT: Introduction: Peyronie's disease (PD) is a fibrotic condition of the tunical layer of corporal penis that can cause deformity, erectile dysfunction, and reduced quality of life in men. Surgical therapy remains an integral treatment of the condition in severe cases. However, there is a paucity of data describing trends in surgical practices. Objective: To characterize the differences between inpatient (IP) and outpatient (OP) practice patterns for PD surgery. We utilized the National Surgical Quality Improvement Program (NSQIP) database to identify and compare factors and outcomes associated with each approach. Methods: NSQIP database was queried for men undergoing PD surgery between 2005-2019. Patients were classified as either OP (<24 hours) or IP(>24 hours). Baseline demographics, operating time, and complications were compared between the two groups. Multivariate logistic regression evaluated factors associated with discharge times and 30-day complications. Results: A total of 924 patients were identified and classified as IP in 157 and OP in 767 patients. Operative time was shorter in OP (89 minutes) compared to IP (126 minutes, p<0.001). A statistically significant difference was noted in comorbidities favoring IP surgery between the groups including chronic obstructive pulmonary disease, anemia, and pre-operative dyspnea. The 30-day complication rates between both groups differed notably for any complication (9.6% IP, 1.6% OP, p< 0.001), any readmission (3.8% IP, 0.7% OP, p 0.005) superficial incisional surgical site infection (5.1% IP, 0.7% IP, p< 0.001), and unplanned intubation (1.3% IP, 0 % OP, p 0.029). Conclusions: Surgical treatment for PD is increasingly utilized as an OP procedure. Patients with shorter operative times and fewer comorbidities appear to be the best suited candidates OP procedures. Beginning in 2015, trends began to shift toward OP procedures. In the era of increasing hospital costs, a shift toward OP surgery for PD has been rising. Disclosure: No